ASSOCIATION OF PROMOTER REGION POLYMORPHISMS OF INTERLEUKIN-10 GENE WITH SUSCEPTIBILITY TO COLORECTAL CANCER: A SYSTEMATIC REVIEW AND META-ANALYSIS - MIRJALILI,Seyed Alireza (2018)
ABSTRACT BACKGROUND: Several epidemiological studies have investigated the association of promoter region polymorphisms of Interleukin-10 (IL-10) gene with colorectal cancer (CRC), while the conclusion is still conflicting and inconclusive. OBJECTIVE: We conducted this meta-analysis to evaluate the association of promoter region polymorphisms of IL-10 with CRC. METHODS: Eligible articles were identified by a search of several bibliographic databases for the period up to March 15, 2018. The strength of the association was measured by odd ratios with 95% confidence intervals. RESULTS: A total of 28 case-control studies with 5,647 CRC cases and 6,908 controls were selected, including 14 studies for IL-10 -1082A>G (rs1800896) polymorphism (2,702 cases and 3,649 controls), eleven studies for -592C>A (rs1800872) polymorphism (3,259 cases and 4,992 controls), and three studies for -819T>C (rs1800871) polymorphism (477 cases and 544 controls). By pooling all eligible studies, we found that the IL-10 -1082A>G and -592C>A polymorphisms were not associated with increased CRC risk in overall population. However, there was significant associations between the IL-10 -819T>C polymorphism and CRC susceptibility under the allele model (A vs G: OR=1.278, 95% CI 1.043-1.566, P=0.018) and the recessive model (AA vs AG+GG: OR=1.709, 95% CI 1.026-2.845, P=0.039). CONCLUSION: In this meta-analysis we found that IL-10 -819T>C polymorphism was associated with significantly increased risk of CRC; while the IL-10 -1082A>G and -592C>A polymorphisms were not associated with CRC risk. The IL-10 -819T>C polymorphism may be important as suspected predictive factor of CRC occurrence.